2020
DOI: 10.18203/2320-1770.ijrcog20200345
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fresh and frozen thawed embryo transfer in terms of clinical pregnancy rate

Abstract: Background: In a standard IVF (in-vivo fertilization) procedure, the embryos formed after the fertilization of male and female gametes are allowed to grow for 3-5 days and then transferred back to the uterine cavity of the female, where they might get attached and start to grow. Objective of this study was to compare clinical pregnancy rate of fresh embryo transfers and frozen-thawed embryo transfers.Methods: This is a retrospective case control study in patients undergoing IVF /ICSI cycles from January 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Furthermore, we observed a higher abortion rate in embryos cultured in 5% O 2 as compared to 2% O 2 (24.7% vs. 11.5%; P = 0.02) in women who underwent FET. While higher abortion rates are reported in women who undergo FET as compared to fresh ET,[ 42 43 ] a study where embryos were exposed either to 5% O 2 or 2% O 2 reported no significant difference in the rate of miscarriage. [ 40 ] However, the numbers in our study in each of these groups are too small to draw any conclusion regarding the abortion rate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed a higher abortion rate in embryos cultured in 5% O 2 as compared to 2% O 2 (24.7% vs. 11.5%; P = 0.02) in women who underwent FET. While higher abortion rates are reported in women who undergo FET as compared to fresh ET,[ 42 43 ] a study where embryos were exposed either to 5% O 2 or 2% O 2 reported no significant difference in the rate of miscarriage. [ 40 ] However, the numbers in our study in each of these groups are too small to draw any conclusion regarding the abortion rate.…”
Section: Discussionmentioning
confidence: 99%